All the stars and teeth eaudiobook - Grace, Adalyn (All the Stars and Teeth, 2020)
"Fierce and unrelenting...Do yourself a favor and get lost in this beautiful book!" — Tomi Adeyemi, #1 New York Times bestselling author of Children of Blood and Bone "Narrator Shayna Small delivers a versatile performance in this young adult fantasy filled with mermaids and magic." — AudioFile Magazine Set in a kingdom where danger lurks beneath the sea, mermaids seek vengeance with song, and magic is a choice, Adalyn Grace's All the Stars and Teeth is a thrilling fantasy for fans of Stephanie Garber's Caraval and Sarah J. Maas's Throne of Glass series. She will reign. As princess of the island kingdom Visidia, Amora Montara has spent her entire life training to be High Animancer—the master of souls. The rest of the realm can choose their magic, but for Amora, it's never been a choice. To secure her place as heir to the throne, she must prove her mastery of the monarchy's dangerous soul magic. When her demonstration goes awry, Amora is forced to flee. She strikes a deal with Bastian, a mysterious pirate: he'll help her prove she's fit to rule, if she'll help him reclaim his stolen magic. But sailing the kingdom holds more wonder—and more peril—than Amora anticipated. A destructive new magic is on the rise, and if Amora is to conquer it, she'll need to face legendary monsters, cross paths with vengeful mermaids, and deal with a stow-away she never expected... or risk the fate of Visidia and lose the crown forever. I am the right choice. The only choice. And I will protect my kingdom. An Imprint Book "Vicious and alluring, All the Stars and Teeth is a force to be reckoned with." —Hafsah Faizal, author of We Hunt the Flame "Jam-packed with swashbuckling adventure, swoonworthy romance, and dark, lush magic." —Christine Lynn Herman, author of The Devouring Gray